Mayank’s Patterntic Theory - Mayank Sharma (International Journal of Indian Psychȯlogy, 2024)
This research introduces Mayank’s Patterntic Theory (MPT), which explores the intricate relationship between the mind and human behavior, addressing the gaps in modern psychological theories. The theory posits that human behavior is governed by three core patterns: P-Patterns, OL-Patterns, and E-Patterns. Through subjective qualitative research, including naturalistic observations, this study examines how these patterns interact to shape individual responses to stimuli, explaining variations in human behavior. The findings suggest that behavioral discrepancies, such as stress, anxiety, and depression, can be attributed to misalignments between these patterns. Additionally, the research provides insights into the potential adverse effects of practices like meditation, the effectiveness of spiritual guidance over professional counselling, and other studies.